Plant-based foods for future: Results of consumer and professional expert interviews in five European countries, EIT-Food Project "The V-Place" - Beate Gebhardt; Klaus Hadwiger (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2020)
[Classification in the EIT Food-Project "The V-Place"] A consortium of partners from science and industry, including the Universities of Hohenheim (UHOH), Aarhus, Bologna and Turin, the companies Danone and Doehler, and the non-governmental organization ProVeg International as consulting partner, is investigating the decisive factors in purchasing decisions for plant-based foods in a two-stage European consumer study in 2020. In the project "The V-Place - Enabling consumer choice in Vegan or Vegetarian food products", the drivers and barriers of plant-based food purchases and the information needs of consumers in the six countries Denmark, France, Germany, Italy, Spain and Poland are also being determined. The leading questions are the following: * Are health, ethical, ecological or completely different reasons the driving forces to buy plant-based foods? * Which reservations and barriers to purchase do consumers have towards plant-based food products? * Do the taste and/or appearance of the alternative products have to come as close as possible to the original - or on the contrary should they be clearly distinguishable? The project is accompanied by background articles as well as social media actions in cooperation with the EIT Food Web platform "FoodUnfolded" (https://www.foodunfolded.com/) which is dedicated to information and entertainment around the topics of food and nutrition. The project is led by the Hohenheim Research Center for Bioeconomy, University of Hohenheim. The Department of Agricultural Markets at the University of Hohenheim is responsible for the qualitative studies. This project is funded by EIT Food, the Food Innovation Community of the European Institute of Innovation and Technology (EIT). EIT is an EU institution under Horizon 2020, the EU Framework Programme for Research and Innovation. The interviews with 70 consumers and professional experts in total, as part one of the two-stage study of "The V-Place" in six European countries, has already been completed. This working paper documents the methodology of the qualitative studies (see chapter 3) and the resulting insights (see chapter 4). We will start with some few theoretical basics and background in chapter 2 and close with an outlook on the next steps.
urn:nbn:de:bsz:100-opus-18353
Keywords: 630